State Cultural Policies in Georgia’s Small Book Market. Case of the Translation Grant Programme “Georgian Literature in Translation” (2010–2018) - Kvirikashvili, Ana (Knygotyra, 2020)
This paper analyses translation support in the Georgian literary field by studying the case of the translation grant program “Georgian Literature in Translation” (2010-2018). Accordingly, it offers a quantitative and qualitative study of the selection of translation projects that have received grants from the Georgian National Book Center as of 2010, when the translation policy program was first launched. This study will consider a) which authors are being promoted by the state and which titles are being translated; b) which publishing houses have benefited the most from these subsidies; and c) which target languages are used in said projects, relying on the frameworks of the sociology of translation (Heilbron and Sapiro). The hypotheses of this paper are 1) that there is a strong impact of the Frankfurt Book Fair and an increase of state-supported translations; 2) a great role of German as a target language in these projects; and 3) relatively active translation flows in the region where Georgia is located. Fieldwork from the 2018 Frankfurt Book Fair will serve as a complementary source, as well as the interviews that I have conducted with agents of the Georgian literary field.